LIVING HADIS DALAM TRADISI PEMBACAAN SHALAWAT ASYGHIL DI MAJELIS TAKLIM AL-HUDA CITEMU KECAMATAN MUDU KABUPATEN CIREBON - Deden Nurjaman; Lukman Zain M S; Ahmad Faqih Hasyim (IAIN Syekh Nurjati Cirebon, 2022)
The tradition of reading the asyghil shalawat is carried out at the Al-Huda Citemutaklim assembly. The practice of asyghil shalawat is praise to Allah and HisMessenger. This research focuses on the study of living hadiths, the meaning ofthe tradition of reciting shalawat asyghil at the Al-Huda taklim assembly, CitemuVillage, Mundu District, Cirebon Regency. The research method uses qualitativedata. The subjects in this study were the asyghil shalawat prayer congregation. The object of this research is the traditional meaning of reciting the asyghil shalawat. Data collection techniques using the method of observation, interviews, and documentation. The results of the research show that the tradition of reciting the asyghil shalawat is a practice based on the Al-Qur'an and hadith. The process of implementing the Asyghil shalawat at the Al-Huda Citemu taklim assembly is carried out every day. Sholawat asyghil is read once after the obligatory prayer and is recited seven times on Friday. The reading of this shalawat is done in congregation. Beginning with reading tawasul to His Majesty the Prophet Muhammad SAW and his family, friends, salafushalih. The meaning of reading the asyghil shalawat for the congregation is to make the heart calm and the soul at peace, feel safe from temptation and seduction, keep away from illness, and keep away from tyranny. Asyghil sholawat is understood in different versions, some of which understand that this asyghil shalawat is a prayer, tasbih, tawasul, istigosah, and the birthday of the Prophet Muhammad SAW.